Inklinasi Masyarakat Muslim Kelas Menengah Terhadap Sekolah Dasar Islam Terpadu di Bandar Lampung - Asiah, Nur; Isnaeni, Ahmad (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2018)
The problem often faced by a contemporary educational institution is the ability to integrate the cognition domain, skills, and noble character in students. On one hand, the existence of qualified educational institutions is constrained by the funding ability of the community. Efforts to improve the quality of educational institutions remain a necessity, particularly addressing the needs of stakeholders. The purpose of this study is to find out and analyse the factors that encourage middle- class Muslim society to make the Integrated Islamic Primary School (SDIT) as a model school. The method used is qualitative with observation and interviews as the data collection techniques. The subject of this study was the parents of the SDIT students surrounding Bandar Lampung. The results of the study are: providing scientific excellence and noble character, providing solutions to busy parents, having a reliable marketing strategy, and having a sense of competition with other excellent public and private schools.